2017
DOI: 10.11646/zootaxa.4350.2.13
|View full text |Cite
|
Sign up to set email alerts
|

New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants

Abstract: Bark and ambrosia beetles from the subfamily Scolytinae are among the most important pests in forests of Northern Iran. During investigations conducted in 2013-2016 in different parts of northern forests, the species Crypturgus cribrellus Reitter, Liparthrum bartschti Mühl, Scolytus varshalovitchi Michalski, Scolytus sulcifrons Rey, Scolytus triarmatus (Eggers) and Trypophloeus granulatus (Ratzeburg) were recorded for the first time in Iran; Trypophloeus and Liparthrum were new genera for Iran. As new host pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 798 publications
(2 citation statements)
references
References 2 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Maksimović (1979) stated that it is one of the most important parasitoids of bark beetles found on Ulmus such as Scolytus multistriatus and S. scolytus species. This species can be distinguished from Table 2 Number of reared hymenoptera species Amini et al (2013) from Guilan province. The most important morphological characters of T. lenkoranus are as follows: Body length is 1.8-2.3 mm, cylindrical, dark brown, covered by long hairs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maksimović (1979) stated that it is one of the most important parasitoids of bark beetles found on Ulmus such as Scolytus multistriatus and S. scolytus species. This species can be distinguished from Table 2 Number of reared hymenoptera species Amini et al (2013) from Guilan province. The most important morphological characters of T. lenkoranus are as follows: Body length is 1.8-2.3 mm, cylindrical, dark brown, covered by long hairs.…”
Section: Resultsmentioning
confidence: 99%
“…Bark beetles are among the most important forest pests of Iran (Amini et al, 2013) and Hymenopterous parasitoids are likely the most effective natural enemies in their biological control (Russo, 1938;Mendel and Dagan, 1986;González and Campos, 1990;Zeiri et al, 2011). In this study, four parasitoid species of bark beetles were identified as E. silesiacus (Ratzeburg, 1848), C. quadrum (Fabricius, 1787), R. maculatus Walker, 1834 andE.…”
Section: Resultsmentioning
confidence: 99%